Harrison's principles of internal medicine - Jameson, J. Larry (ed.) (New York Mc Graw Hill Education, 2018)
One of the most esteemed names in the field of medicine, 'Harrison's Principle of Internal Medicine captures the entire plethora of developments, innovations and advancements in the field of medicine. The 19th edition of the book brings home the updated content related clinical trials, disease pathogenesis, current diagnostic methods and imaging, newly approved and established treatment methods and evidence-based guidelines of practice. The 'Harrison?s Principle of Internal Medicine 19th Edition? comes in a set of two books. The first book the basic foundation principles, the cardinal manifestation of diseases and approach to differential diagnosis. The second book, on the other hand, covers disease pathogenesis and their respective treatments. Besides, important topics related to men?s health, fatigue, impact of global warming on infectious diseases have also been covered in this new edition along with critical updates in therapeutics and management in a varied range of diseases have also been added. The diseases include diabetes, hepatitis, Ebola virus diseases, Lipoprotein disorders, AIDS and HIV along many others. Harrison?s have always been famous for their clinical algorithms. This edition contains an increased number of those along with clinical-pathological images in proper colours, full coloured illustrations and drawings to help the students and practitioners understand the concepts better. The edition also contains great access to multimedia resources related to essential bedside techniques, endoscopic findings, techniques of physical examinations and cardiovascular findings among others
Keywords: Internal medicine